Sistem Informasi Pemesanan Rumah Makan Dapur Eladhia Berbasis Web - Boby Yudistira; Nurahman Nurahman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The application of information technology causes changes in work habits. That the development of information systems has penetrated into the business world, including the Eladhia Kitchen Restaurant, although it is still a new restaurant, many Sampit residents have begun to come to Eladhia's Kitchen Restaurant. This restaurant business has many transactions with consumers. However, it is hindered by the absence of informative online media for ordering that explains in detail the food offered as a promotional medium to facilitate ordering by customers for food and beverages. manual, and the transaction process is not properly archived so that business owners find it difficult to know the amount of income each month. In order for the management of order and payment transactions to be carried out effectively, a Restaurant Order information system is created that contains User Data, Product Data, Order Data, Payment Data, Order Data Reports and Payment Data Reports